Minha trajetória no curso Medicina UFSCar - Pereira, Vinicius Miranda (Universidade Federal de São Carlos, 2021)
This paper intends to narrate the 6-year trajectory of a medical student at the Universidade Federal de São Carlos. Through a narrative divided into the three cycles of the course, it tells how each moment impacted and was defined for academic and personal development. The paper ends with the extracurricular activities carried out and concludes that respect for others is the greatest learning that one can take away.
My trajectory in the UFSCar Medicine Course
Keywords: Educação de graduação em medicina; Aprendizagem Baseada em Problemas; Narrativa pessoal; CIENCIAS DA SAUDE::MEDICINA::CLINICA MEDICA